The vacationers [large type] - Straub, Emma (Wheeler Publishing, 2014)
For the Posts, a two-week trip to the island of Mallorca with their extended family and friends is a celebration: it's Franny and Jim's thirty-fifth anniversary, and their daughter has graduated from high school. The sunlit island also promises an escape from the tensions simmering at home. But all does not go according to plan: secrets come to light, old and new humiliations are experienced, childhood rivalries resurface, and ancient wounds are exacerbated.